(untitled) (Research, Society and Development, 2021)
Additive Manufacturing (AM) has been considered an innovative technology for the development of orthoses. Even so, the use of AM, utilizing low cost rigid and flexible material which can be used in different ways by the same user, to produce a modular orthosis has yet to be explored. Purpose: Develop a modular wrist, hand and finger orthosis that can be utilized as a functional or static orthosis, depending on the therapeutic objective. This being produced by low cost Additive Manufacturing, through a single anatomy acquisition process. Approach: Firstly, requirements for modularization and development were defined in a team with occupational therapists and mechanical engineers, After indirect anatomy acquisition of a volunteer, without disabilities, two parts of the same orthosis were modeled, one flexible (functional) and the other rigid (static). These were printed on PLA (rigid part) and flexible TPU (functional part) with an Open Source printer. In addition, fastening strips were also made in flexible TPU. Findings: Three parts of which make up the modular orthosis were produced. This can be used in two different ways; one being to maintain the static posture of the wrist, hand and fingers and the other to provide functionality of the hands, but with the correct positioning of the wrist and thumb. Originality: Even with low-cost material and an open source machine, it was possible to generate an innovative proposal with the use of AM as the orthosis manufacturing process.